(untitled) (Altre Modernità, 2016)
Maria Vittoria Calvi, Irina Bajini e Milin Bonomi (a cura di), Lingue migranti e nuovi paesaggi (Milano, LED, 2015, 240 pp. ISBN 978-88-7916-700-0) di Valentina Paleari